An Orthognathine Weevil of the Genus Mesocordylus in Dominican Amber (Coleoptera: Curculionoidea: Dryophthoridae). - Davis, Steven R.; Engel, Michael S. (Contributions to Entomology = Beiträge zur Entomologie, 2009)
A new orthognathine weevil species (Curculionoidea: Dryophthoridae), Mesocordylus longiscapus sp. n., is described and illustrated from Early Miocene Dominican amber. It represents the first amber fossil record of Mesocordylus and the second for the subfamily Orthognathinae.KeywordsTertiary, Caribbean, paleontology, Polyphaga, taxonomy.Nomenclatural Actslongiscapus Davis & Engel, 2009 (Mesocordylus), spec. n.